Strategic Learning and its Impact on Human Resource Management Practices: Analytical research in the Directorate of Training and Rehabilitation of the Ministry of the Interior (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research test the performance test of the strategic application in human resource practices and the identification of   exercise in exercise practice, psychology, strategic training, training, training, research plans, descriptive and analytical approach, and to achieve the research objective. Shown here is a set of songs, actresses, statistical, programs (SMART PLS V.3.3-SPSS V.24-). Excel) for data analysis, data simplification, data simplification, standard deviation, arithmetic mean, correlation coefficient, simple regression model). Among the most important findings of the research, the Directorate has invested strategic learning in human resource practices well in directing knowledge, initiating knowledge, interpreting it and teaching it that begins to improve it directly, and the research concluded with a group of the most important of which is the interest in additional interest in human resource management practices in directing strategic learning in its dimensions in improving it